Comparing economic policy reforms in Vietnam and China: Institutional and political dynamics towards a market economy - Hecita, Ian Jayson R. (Animo Repository, 2005)
The emergence of China in global economy has been attributed to the eventual success of economic policy reforms from centrally planned to a market economy. In the same way, Vietnam has an enthusiastic economy relative to its Southeast Asian neighbors after the implementation of the Doi Mot. These success stories of economic reforms are contextualized in the lack of political reforms and the dominance of the party state in both economies; hence it makes the study and comparison of both transitory and developmental state interesting and relevant. This study examines the policy performance of Vietnam and China after the economic policy reforms were implemented (and are still being implemented). The divergences and the convergences in the performance of a policy reform (outcome/ impact), --the extent and quality of a policy (content), the policy process and policy output are analyzed in the theoretical background of institutionalism/ structuralism and institutional/policy dynamics. The rationale of the paper is to illustrate how institutions (state policies, government structures, socio economic institutions, etc.) and its dynamics affect the performance of economies in a reform process.